Neue Kunst aus Dresden. - BASF-Feierabendhaus, Ludwigshafen (Ludwigshafen am Rhein : BASF Aktiengesellschaft, 1989)
Göschel, Eberhard ; Hampel, Angela ; Jackisch, Matthias ; Krause, Wolfgang ; Maasdorf, Frank ; Smy, Wolfgang ; Böckelmann, Paul ; Fleischer, Lutz ; Hegewald, Andreas ; Just, Christiane ; Kasten, Petra ; Lewandowsky, Volker ; Sandner, Reinhard ; Sonntag, Jörg
Neue Kunst aus Dresden, BASF-Feierabendhaus, Ludwigshafen am Rhein, 26. Februar bis 18. April 1989
boek
Keywords: Dresden